Kinerja Keuangan dan Ukuran Perusahaan terhadap Harga Saham dengan Kebijakan Dividen sebagai Variabel Intervening - Rico Wijaya Z (Jurnal Keuangan dan Perbankan, 2017)
This was research conducted to examine the effect of the leverage ratio, activity ratio, and size firm on stock price with dividend policy as a mediating variable the companies listed in Indonesia Stock Exchange 2012-2014. This research has a total number of samples 141 samples and using purposive sampling with criteria declare a dividend payout for 3 consecutive years, and the debt to equity ratio, total asset turnover, which is positive. The first result is total asset turnover, Ln_total asset have positive effect on dividend payout ratio, and debt to equity don’t have positive effect on dividend payout ratio. The second result is total asset turnover, Ln_total assets, and dividend payout ratio have positive effect on Ln_stock prices and debt to equity don’t have positive effect on Ln_stock prices. Test results mediating dividend payout ratio is not proven mediates the relationship debt to equity, total asset turn over, and Ln_total asset on Ln_stock prices. The result of this research proves that there is no influence of dividend policy in relation of financial performance to stock price.